Development of novel self-assembled polymeric micelles from partially hydrolysed poly(2-ethyl-2-oxazoline)-co-PEI-b-PCL block copolymer as non-viral vectors for plasmid DNA in vitro transfection. (12th November 2018) - Kara, Asli; Ozturk, Naile; Esendagli, Gunes; Ozkose, Umut Ugur; Gulyuz, Sevgi; Yilmaz, Ozgur; Telci, Dilek; Bozkir, Asuman; Vural, Imran
Abstract: A new efficient, non-viral gene delivery cationic polymeric micellar system was developed by partial hydrolysis of poly(2-ethyl-2-oxazoline) (PEtOx) with two different hydrolysis percentages of PEtOx (30% and 60%) to reduce the disadvantages of the PEI. These self-assemble amphiphilic cationic micelles prepared from poly(2-ethyl-2-oxazoline)30% - co -poly(ethyleneimine)-block-poly(ɛ-caprolactone) (PEtOx30% - co -PEI- b -PCL) (PPP30) and poly(2-ethyl-2-oxazoline) 60% - co -poly(ethyleneimine)-block-poly(ɛ-caprolactone) (PEtOx60% - co -PEI- b -PCL) (PPP60) block copolymers were successfully condensed with pEGFP-C3 plasmid DNA via electrostatic interactions to form micelle/DNA complexes with desirable particle sizes. All formulations showed low critical micelle concentration (CMC) values that means highly stable in serum containing medium. Polymeric micelles were also evaluated for their stability in the presence of serum and nuclease as well as cytotoxicity and transfection efficiency. All our results proved that our novel polymeric micellar system prepared by PPP60 block copolymer offer to be an efficient promising carrier for gene delivery applications. Moreover, these findings contribute to design and development of novel gene vectors with tunable and functionality features and also to reduce the cytotoxicity of PEI by partial hydrolysis of PEtOx an alternative synthesis method to produce linear PEI. Abstract :